The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fncel.2023.1135227
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture treatment ameliorates depressive-like behavior and cognitive dysfunction via CB1R dependent mitochondria biogenesis after experimental global cerebral ischemic stroke

Abstract: IntroductionThis study aimed to identify the effect of electroacupuncture (EA) treatment on post-stroke depression (PSD) and explore whether cannabinoid receptor 1 (CB1R)-mediated mitochondrial biogenesis accounts for the treatment effect of EA.MethodsThe PSD mouse model was induced by a consecutive 14-day chronic unpredictable stress operation after 7 days of recovery from the bilateral common carotid artery occlusion surgery. Either EA treatment or sham stimulation was performed for 14 consecutive days from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Global cerebral ischemia (GCI) is a complex disorder that results from a wide range of pathologic events, including asphyxia, arrhythmia, cardiac arrest, and shock ( Neumann et al, 2013 ; Farajdokht et al, 2022 ). Due to the susceptibility of regions such as the hippocampus and cortex to ischemic insults, GCI is commonly accompanied by psychiatric disorders ( Hu et al, 2023 ). However, from an etiological standpoint, the physical and psychological stress caused by movement restriction and high dependency on caregivers may lead to intense negative emotions in subjects ( Farajdokht et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global cerebral ischemia (GCI) is a complex disorder that results from a wide range of pathologic events, including asphyxia, arrhythmia, cardiac arrest, and shock ( Neumann et al, 2013 ; Farajdokht et al, 2022 ). Due to the susceptibility of regions such as the hippocampus and cortex to ischemic insults, GCI is commonly accompanied by psychiatric disorders ( Hu et al, 2023 ). However, from an etiological standpoint, the physical and psychological stress caused by movement restriction and high dependency on caregivers may lead to intense negative emotions in subjects ( Farajdokht et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, almost all antidepressants [selective serotonin reuptake inhibitors (SSRIs), serotonin and noradrenaline reuptake inhibitors, and monoamine oxidase inhibitors] are associated with increased risks of adverse outcomes, including mortality, suicide, hemorrhagic complications, bone fractures, and seizures ( Li et al, 2022 ), and patients may exhibit treatment-refractory response and poor adherence to antidepressant drugs. Increasing attention has been paid to the application of EA for alleviating depressive symptoms after stroke, in light of their few side effects and lower cost ( Kang et al, 2021 ; Hu et al, 2023 ). However, despite the thriving evidence proving the remarkable therapeutic efficacy of EA for PID in clinical practice and randomized controlled trials, there are considerably fewer basic experiments regarding EA’s effects at the cellular level, particularly on neural cell types besides neurons, and this, to some extent, may limit our understanding of the mechanism of EA.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition, some animal studies have found that EA treatment ameliorated depression-like behaviors by modulating the tPA/BDNF/TrkB signaling pathway in the prefrontal cortex. 17 However, till now, it is unknown whether AMPK-mediated mitochondrial function participates in the protective effects of EA treatment on PSD.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of mitochondrial function-related proteins was found to be decreased in PSD rats, whereas EA treatment reversed these changes. 17 Based on this, we investigated the involvement of AMPK-mediated mitochondrial activity in the antidepressant effects of EA for the first time. Our results suggest that EA increased the endogenous p-AMPK expression and alleviated PSD-induced mitochondrial dysfunction, whereas blocking AMPK expression partially blocked the therapeutic effect of EA.…”
mentioning
confidence: 99%